Does open innovation apply to China? Exploring the contingent role of external knowledge sources and internal absorptive capacity in Chinese large firms and SMEs. (11th March 2015) - Huang, Fang; Rice, John; Martin, Nigel
Abstract: While 'open innovation' is often considered to be an organisational strategy with universal application, its generalisability and applicability to organisations operating within emerging economies has yet to be fully explored. This study provides empirical evidence of its importance within a substantial sample of Chinese large firms and small and medium enterprises. Using Tobit regression analysis, our findings indicate that external knowledge sources from inter-firm networking are more important in creating the benefits of open innovation for Chinese small and medium enterprises than their larger peers. Linkages to university and research institutes generally have few direct effects on the innovation performance of both large and small firms in China. However, the role of universities and research institutes is shown to be important among our large firm sample when combined with evident internal absorptive capacity. This interaction is generally limited to our large firm sample, and is not as evident among small firms. Our study indicates that the barriers to the adoption of open innovation by Chinese firms might be largely related to the comparatively weak domestic research expertise and limited organisational absorptive capabilities, with this most particularly evident for small and medium enterprises. These findings suggest that, based on this evidence, there is no need for emerging economies like China to mimic the emergence path from closed to open innovation followed by developed countries. Chinese firms will be more likely to garner the benefits available from openness when they develop the capabilities required to identify, assimilate and commercialise knowledge and technologies obtained from external sources.